Protocol for a randomised controlled trial of 90% kanuka honey versus 5% aciclovir for the treatment of herpes simplex labialis in the community setting. Issue 8 (3rd August 2017) - Semprini, Alex; Singer, Joseph; Shortt, Nicholas; Braithwaite, Irene; Beasley, Richard
Abstract : Introduction: Worldwide, about 90% of people are infected with the herpes simplex virus, 30% of whom will experience recurrent herpes simplex labialis, commonly referred to as 'cold sores', which can last up to 10 days. The most common treatment is aciclovir cream which reduces healing time by just half a day compared with no specific treatment. This is a protocol for a randomised controlled trial (RCT) to determine the efficacy of medical grade kanuka honey-based topical treatment (Honevo) in reducing the healing time and pain of cold sores, compared with topical aciclovir treatment (Viraban). Methods and analysis: This open-label, parallel-group, active comparator superiority RCT will compare the efficacy of medical grade kanuka honey with 5% aciclovir cream in the treatment of cold sores in the setting of a pharmacy research network of 60 sites throughout New Zealand. Adults presenting with a cold sore (N=950) will be randomised by pharmacy-based investigators. The pharmacy-based investigators will dispense the investigational product to randomised participants and both study groups apply the treatment five times daily until their skin returns to normal or for 14 days, whichever occurs first. In response to a daily SMS message, participants complete an assessment of their cold sore healing, with reference to a visual guide, and transmit it to the investigators by a smartphone eDiary in real time. The primary outcome variable is time (in days) from randomisation to return to normal skin. Secondary endpoints include total healing time stratified by stage of the lesion at onset of treatment, highest pain severity and time to pain resolution. Ethics and dissemination: New Zealand Ethics Registration 15/NTB/93. Results will be published in a peer-reviewed medical journal, presented at academic meetings and reported to participants. Trial registration number: Australia New Zealand Clinical Trials Registry: ACTRN12615000648527, pre-results. SCOTT Registration: 15/SCOTT/14 Protocol version: 4.0 (12 June 2017)